Funcionamiento familiar y autoestima en el riesgo de consumo de drogas en adolescentes. Institución Educativa Estatal "César Vallejo" - La Esperanza, 2007 - Rumay Chanduco, Doris (2007)
The present research, correlational descriptive type and cross section, was made in the Public Educative Institution “Cesar Vallejo” of the destrict La Esperanza, during the months of February to November 2007, in order to determine the relation that exists between the familiar functioning and self-esteem in drug consumption risk in adolescents. The universal sample was constituted by 280 adolescents from fourth and fifth year of secondary. For the data collection 3 instruments were used: Scale of real and ideal familiar functioning of Olson, self-esteem test school form of Coopersmith and the Survey on the drug consumption in adolescents of Tarter. The obtained data was processed and analyzed by means of the statistical tests square Chi and the correlation of Pearson; the results are presented in charts and graphics. The results indicated that: The adolescents show a high familiar functioning 47.5 percent, and an average selfesteem level 78 percent. The 67.1 percent of the adolescents consumes some type of drug; being the alcohol the legal drug of greater consumption with 63.9 percent, followed by tobacco with 32.5 percent, and the illegal drug of greater consumption the marijuana with 10.4 percent. The age of beginning of the consumption 14 years old. The drug consumption is increased in smaller familiar functioning and smaller selfesteem level. There exists highly meaningful relation between the familiar functioning and the drug consumption in adolescents. P =0.000<0.005. There exists highly meaningful relation between the self-esteem level and the drug consumption in adolescents. P = 0.000<0.05. There also exists highly meaningful relation between the familiar functioning and selfesteen and the drug consumption in adolescents. P = 0.000<0.05. The familiar functioning to influence the drug consumption in adolescents because to influence the development of the self-esteem.